2017
DOI: 10.1016/j.cmet.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation of T Cell Longevity and Function in Tumor Immunotherapy

Abstract: Summary Cancer immunotherapy is an increasingly successful strategy for the treatment of patients who have advanced or conventional therapy-resistant cancers. T cells are key mediators of tumor destruction and their specificity for tumor-expressed antigens is of paramount importance, but other T cell-intrinsic qualities such as durability, longevity and functionality also play important roles in determining the efficacy of immunotherapy. The cellular energetic pathways that are utilized by T cells play a key r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
353
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(357 citation statements)
references
References 176 publications
(257 reference statements)
4
353
0
Order By: Relevance
“…Adoptive immunotherapy has manifested significant, sometimes curative, therapeutic effects in treating certain types of cancer. Recent studies have shown that T cell metabolic attributes largely shape donor T cell persistence and memory development, which are key determinants of therapy efficacy (Kawalekar et al, 2016; Kishton et al, 2017; Sukumar et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Adoptive immunotherapy has manifested significant, sometimes curative, therapeutic effects in treating certain types of cancer. Recent studies have shown that T cell metabolic attributes largely shape donor T cell persistence and memory development, which are key determinants of therapy efficacy (Kawalekar et al, 2016; Kishton et al, 2017; Sukumar et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…During T‐cell differentiation from naïve to terminally differentiated T cells, anabolic metabolism increases and generates biosynthetic intermediates, such as nucleotides, in a process similar to the Warburg effect. It has also been reported that reducing T‐cell glycolysis during T‐cell expansion for immunotherapy can maintain the T‐cell replicative capacity and longevity to mediate a successful immune anti‐cancer effect in vivo; this can be achieved using pharmacological interventions to modulate T‐cell metabolism . To date, there are few studies investigating PKM2 in relation to immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking glycolytic metabolism in young CD8 T cells has been shown to promote generation of long‐lived, functional memory populations, while enforcing glycolysis drives CD8 T cells towards a terminally differentiated state . One way to prevent accumulation of terminally differentiated senescent T cells and promote survival of functional memory T cells in advanced age could include inhibitors or regulators of glycolysis, such as 2‐deoxyglucose, which directly inhibits glycolysis or metformin, which indirectly decreases glycolysis via activation of AMPK …”
Section: Metabolic Interventions To Improve T Cell Immunity In the Elmentioning
confidence: 99%